The rape of the lock - Pope, Alexander (Hesperus London, 2004)
This edition of Alexander Pope's famous poem, "The Rape of the Lock," includes an introduction and notes by Clarence Tracy, providing insights and historical context to Pope$1 (Bs work. It$1 (Bs designed to offer a deeper understanding of the poem through visual and explanatory elements that enhance the reader$1 (Bs comprehension of the text and its referencess